An evolutionary perspective on the behavioral consequences of exogenous oxytocin application - Ebitz, R B.; Platt, Michael M. (Frontiers in Behavioral Neuroscience, 2014)
Oxytocin (OT) is released in response to social signals, particularly positive ones like eye contact, social touch, sexual behavior, and affiliative vocalizations. Conversely, exogenous delivery of OT has diverse behavioral effects, sometimes promoting affiliative and prosocial behaviors, but sometimes suppressing them. Here, we argue that one unifying interpretation of these diverse effects is to view OT as an evolutionarily conserved physiological signal indicating affiliative interactions and predicting their behavioral consequences. In this model, OT regulates the way information about the social environment accesses the neural circuitry responsible for social behavior, thereby shaping it in sometimes counterintuitive but adaptive ways. Notably, prosociality is not always the most adaptive response to an affiliative signal from another individual. In many circumstances, an asocial or even antisocial response may confer greater fitness benefits. We argue that the behavioral effects of exogenous OT delivery not only parallel the behavioral effects of affiliative interactions, but are themselves adaptive responses to affiliative interactions. In support of this idea, we review recent evidence that OT does not unilaterally enhance social attention, as previously thought, but often reduces the salience of social signals in the environment. Such diminished social vigilance may be an adaptive response to affiliative social interactions because it frees attentional resources for the pursuit of other goals. Finally, we predict that OT may mediate other behavioral consequences of social interactions, such as reduced predator vigilance, and argue that this is a rich avenue for future behavioral and neurobiological study.